2007
DOI: 10.1073/pnas.0704816105
|View full text |Cite
|
Sign up to set email alerts
|

The role of Pleistocene refugia and rivers in shaping gorilla genetic diversity in central Africa

Abstract: The role of Pleistocene forest refugia and rivers in the evolutionary diversification of tropical biota has been the subject of considerable debate. A range-wide analysis of gorilla mitochondrial and nuclear variation was used to test the potential role of both refugia and rivers in shaping genetic diversity in current populations. Results reveal strong patterns of regional differentiation that are consistent with refugial hypotheses for central Africa. Four major mitochondrial haplogroups are evident with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
200
5
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(221 citation statements)
references
References 80 publications
14
200
5
2
Order By: Relevance
“…Along with historical factors (mainly, colonization history), environmental heterogeneity (for example, rainfall levels (Letouzey, 1968)) and physical barriers (for example, rivers (Anthony et al, 2007)) are key factors that have already been demonstrated in Africa to influence species distribution, and thus their genetic structure, but mostly for animals species. Another potential ecological barrier is due to the annual movement of the intertropical convergence zone, a band of clouds that encircles the globe near the thermal equator and determines the seasonality of precipitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with historical factors (mainly, colonization history), environmental heterogeneity (for example, rainfall levels (Letouzey, 1968)) and physical barriers (for example, rivers (Anthony et al, 2007)) are key factors that have already been demonstrated in Africa to influence species distribution, and thus their genetic structure, but mostly for animals species. Another potential ecological barrier is due to the annual movement of the intertropical convergence zone, a band of clouds that encircles the globe near the thermal equator and determines the seasonality of precipitations.…”
Section: Discussionmentioning
confidence: 99%
“…In D. benthamianus, a (slight) relationship exists between belonging to a genetic cluster and some 'environmental' heterogeneity (presence of 'mountains' and localization of the thermal equator), contrary to Aucoumea (Born, 2007). The riverine barrier hypothesis, which has been verified with respect to the structure of genetic diversity mainly in primates (Eriksson et al, 2004;Anthony et al, 2007), remains largely untested in plants, notably in African rainforests.…”
Section: Discussionmentioning
confidence: 99%
“…Remnant rainforest areas have been hypothesized as glacial refugia for many organisms, for example, in Africa [19][20][21] and the New World [22]. Empirical studies have provided indirect or less commonly direct evidence that species distributions and endemism patterns can indeed be associated with Quaternary-scale habitat stability in tropical areas [7,23,24]. Today, vegetation distribution in the tropics is primarily controlled by precipitation [25], which also plays a particularly important role as the main driver of species richness at low latitudes [3].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that ape populations separated by rivers have been genetically distinct for hundreds of thousands of years (Anthony et al 2007;Fünfstück et al 2014), while forests are usually hunted out for several kilometres on either side of national roads and are subsequently avoided by wildlife. Of these 18 priority landscapes, 14 are larger than 10,000 km² and only one is smaller than 5,000 km² in size; 17 each harbour more than 5,000 great apes; 11 had great ape densities of >1 indiv./km²; 16 >0.5 indiv./km², and five are transboundary landscapes straddling international boundaries.…”
Section: Identification Of Priority Landscapesmentioning
confidence: 99%